An Investigation of the Characteristics and Performance of Hybrid Routing Protocol in (MANET) - Ismael Al-Sanjary, Omar; Abdullah Ahmed, Ahmed; Majeed Zangana, Hewa; A.M Ali, Musab; Hazim Alkawaz, Mohammed; Hameed Aldulaimi, Saeed (International Journal of Engineering and Technology, 2018)
Mobile ad hoc network (MANET) is a set of nodes, which communicates using wireless medium and forming an arbitrary and dynamic network. Data is transmitted by forwarding the data from one node to another. To achieve this, each MANET node must act as both a host and a routing node. Routing in MANET poses a challenge because of the frequent changes in network topology in addition to the limited resources available for each node. Many different routing protocols have developed for MANET but in general, they can be categorized into three categories, which are proactive, reactive, and hybrid routing protocols. Hybrid routing protocols are interesting because they combine the characteristics of both proactive and reactive routing protocols. In this paper, we study the characteristics of a hybrid routing protocol (ZRP) and then compare its performance with a proactive (FSRL) and reactive (AODV) routing protocols.Â Â